2007
DOI: 10.1677/joe-06-0198
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin D receptor and its ligand 1α,25-dihydroxyvitamin D3 in Atlantic salmon (Salmo salar)

Abstract: Seaward migration of Salmo salar is preceded by preparatory physiological adaptations (parr-smolt transformation) to allow for a switch from freshwater (FW) to seawater (SW), which also means a switch in ambient calcium from hypocalcic (!1 mM Ca 2C ) to the plasma (w1 . 25 mM Ca 2C ) and to strongly hypercalcic (8-12 mM Ca 2C ). Uptake, storage (skeleton, scales) and excretion of calcium need careful regulation. In fish, the vitamin D endocrine system plays a rather enigmatic role in calcium physiology. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Enzymes capable of metabolizing vitamin D into more polar metabolites already emerged early in the evolution of life as shown in plants, snails and crustacean (see above) but it is unknown whether this involves P450/CYP proteins. Several bacteria express CYP enzymes capable to produce 1,25(OH) 2 D 3 with high efficacy but the relation of these CYP107 54 There are several P450 enzymes with highly selective activity for vitamin D metabolism such as CYP2R1 (25-hydroxylation of vitamin D), CYP27B1 (1a-hydroxylation of 25OHD) and CYP24A1 (24R-hydroxylation of 25OHD) but the evolutionary origin of these CYP genes in chordates and early vertebrates is not well defined. Zebrafish, however, clearly express CYP27B1 and CYP24A1.…”
Section: Origin Of the Vitamin D Endocrine System In Vertebratesmentioning
confidence: 99%
“…Enzymes capable of metabolizing vitamin D into more polar metabolites already emerged early in the evolution of life as shown in plants, snails and crustacean (see above) but it is unknown whether this involves P450/CYP proteins. Several bacteria express CYP enzymes capable to produce 1,25(OH) 2 D 3 with high efficacy but the relation of these CYP107 54 There are several P450 enzymes with highly selective activity for vitamin D metabolism such as CYP2R1 (25-hydroxylation of vitamin D), CYP27B1 (1a-hydroxylation of 25OHD) and CYP24A1 (24R-hydroxylation of 25OHD) but the evolutionary origin of these CYP genes in chordates and early vertebrates is not well defined. Zebrafish, however, clearly express CYP27B1 and CYP24A1.…”
Section: Origin Of the Vitamin D Endocrine System In Vertebratesmentioning
confidence: 99%
“…Excessive intake of vitamin D 3 depressed the growth rate of channel catfish (Andrews et al, 1980) and rainbow trout (O. mykiss) (Vielma et al, 1998). The vitamin D endocrine system plays a crucial role in calcium and phosphorus handling during parr-smolt transformation in Atlantic salmon (Salmo salar) (Lock et al, 2007). However, Rao and Raghuramulu (1999) reported that vitamin D 3 probably played no role in Ca or P metabolism in tilapia (Oreochromis spp.).…”
Section: Tablementioning
confidence: 99%
“…In fish, vitamin D is reported to be involved in normal growth, development, bone mineralization, and Ca and P homeostasis (Lock et al, 2007). There is evidence that supplementation of diets with vitamin D is an effective method in increasing phytate hydrolysis in broiler chickens (Mitchell and Edwards, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In fish, vitamin D 3 had been demonstrated to elevate serum Ca 2+ level [20], [21] .Vitamin D 3 was also proposed to be associated with Ca 2+ transport in the gills based on the vitamin D 3 deficiency-induced impairment of growth and mineralization in the fish skeleton [22], [23]. Indeed, changes in the plasma levels of 1,25 (OH) 2 D 3 or mRNA expression of gill/kidney VDR have been observed in salmon undergoing smoltification and migrating from freshwater (low Ca 2+ concentrations) to seawater (high Ca 2+ concentrations), suggesting that synthesis of the sterol and its receptor might be regulated depending upon ambient Ca 2+ concentrations [23]. In mammals, glucocorticoid has been well documented to affect vitamin D 3 metabolism although the actions varied depending on species [24][29].…”
Section: Introductionmentioning
confidence: 99%